EASL Clinical Practical Guidelines on the management of acute (fulminant) liver failure - Wendon, Julia; Cordoba, Juan; Dhawan, Anil; Larsen, Fin Stolze; Manns, Michael; Nevens, Frederik; Samuel, Didier; Simpson, Kenneth J.; Yaron, Ilan; Bernardi, Mauro (Journal of hepatology, 2017)
The term acute liver failure (ALF) is frequently applied as a generic expression to describe patients presenting with or developing an acute episode of liver dysfunction. In the context of hepatological practice, however, ALF refers to a highly specific and rare syndrome, characterised by an acute abnormality of liver blood tests in an individual without underlying chronic liver disease. The disease process is associated with development of a coagulopathy of liver aetiology, and clinically apparent altered level of consciousness due to hepatic encephalopathy. Several important measures are immediately necessary when the patient presents for medical attention. These, as well as additional clinical procedures will be the subject of these clinical practice guidelines.